Internal Audit in Turkish Public Finance Management (Uluslararası Uygulamalı Ekonomi ve Finans Çalışmaları Dergisi, 2016)
Turkish Public Finance faced with "Internal Audit Institution" with Public Financial Administration and Control Law (law number 5018) in 2006.  Internal audit has entered into legislation in the light of the principles of transparency and accountability, with the purpose of using public resources effectively, economically and efficiently. This study aims to determine the operational status of the internal audit of public administrations. In this context, by examining the relevant parts of the law with the document scanning method, according to Internal Auditor positions allocated to the public administration, the numbers were determined. Staff allocated to the public administrations of the 47% is made up of as the Internal Auditor. But Internal Auditor has not been appointed to the most important institutions of the state yet. This has been identified as the lack of legal obligation.